Genotoxicity Revaluation of Three Commercial Nitroheterocyclic Drugs: Nifurtimox, Benznidazole, and Metronidazole - Annamaria Buschini; Lisa Ferrarini; Susanna Franzoni; Serena Galati; Mirca Lazzaretti; Francesca Mussi; Cristina Northfleet de Albuquerque; Tânia Maria Araújo Domingues Zucchi; Paola Poli (Journal of Parasitology Research)
Nitroheterocyclic compounds are widely used as therapeutic agents against a variety of protozoan and bacterial infections. However, the literature on these compounds, suspected of being carcinogens, is widely controversial. In this study, cytotoxic and genotoxic potential of three drugs, Nifurtimox (NFX), Benznidazole (BNZ), and Metronidazole (MTZ) was re-evaluated by different assays. Only NFX reduces survival rate in actively proliferating cells. The compounds are more active for base-pair substitution than frameshift induction in Salmonella; NFX and BNZ are more mutagenic than MTZ; they are widely dependent from nitroreduction whereas microsomal fraction S9 weakly affects the mutagenic potential. Comet assay detects BNZ- and NFX-induced DNA damage at doses in the range of therapeutically treated patient plasma concentration; BNZ seems to mainly act through ROS generation whereas a dose-dependent mechanism of DNA damaging is suggested for NFX. The lack of effects on mammalian cells for MTZ is confirmed also in MN assay whereas MN induction is observed for NFX and BNZ. The effects of MTZ, that shows comparatively low reduction potential, seem to be strictly dependent on anaerobic/hypoxic conditions. Both NFX and BNZ may not only lead to cellular damage of the infective agent but also interact with the DNA of mammalian cells.